Characterization of Polymer Surfaces by the Use of Different Wetting Theories Regarding Acid-Base Properties - Eduard Kraus; Lukas Orf; Michael Heilig; Benjamin Baudrit; Irina Starostina; Oleg Stoyanov (International Journal of Polymer Science)
The existing wetting methods for the determination of acid-base properties on solid surfaces are discussed. Striving for a better understanding of the adhesive polymer interactions in adhesively joined polymers, the methods of Berger and van Oss-Chaudhury-Good were found as the most suitable methods for the investigation of wetting on solid polymer surfaces. Methods of nonlinear systems by Della Volpe and Siboni were adapted and evaluated on plastic surfaces. In the context of these investigations various data of the surface free energy as well as its components have been identified for a number of polymer surfaces by application of spatial equation solutions.